Do we have a magic bullet to treat moderate and severe anemia in pregnant women? - Shashi Kant (Wolters Kluwer Medknow Publications, 2019)
A desperate situation may evoke a fundamental question or suggestion of a radical solution. Hence, let us first examine whether the current situation of maternal anemia in India is really desperate and therefore merits a search for a "magic bullet" as a cure.